Group G Streptococcal Bacteremia in Jerusalem - Cohen-Poradosu, Ronit (Centers for Disease Control and Prevention, 2004)
Group G Streptococcus (GGS) can cause severe infections, including bacteremia. These organisms often express a surface protein homologous to the Streptococcus pyogenes M protein. We retrospectively studied the characteristics of patients from the Hadassah Medical Center with GGS bacteremia from 1989 to 2000. Ninety-four cases of GGS bacteremia were identified in 84 patients. The median age was 62 years, 54% were males, and 92% had underlying diseases (35% had a malignancy, and 35% had diabetes mellitus). The most frequent source for bacteremia was cellulitis (61%). emm typing of 56 available isolates disclosed 13 different types, including 2 novel types. Six patients had recurrent bacteremia with two to four bacteremic episodes, five had chronic lymphatic disorders, and two had emm type stG840.0 in every episode. Recurrent bacteremia has not been described for invasive group A Streptococcus. We describe an entity of recurrent GGS bacteremia, which is associated with lymphatic disorders and possibly with emm stG840.0.